Privatization in Ukraine : Challenges of Assessment and Coverage in Fund Conditionality - Elborgh-Woytek, Katrin (IMF Policy Discussion Papers; Policy Discussion Paper, 2002)
The paper examines the recent privatization experience in Ukraine in the context of the streamlining of Fund structural conditionality. A particular focus is the shift from privatization-related conditionality based on quantitative targets to conditionality aimed at strengthening privatization procedures. The paper examines how this shift was managed in Ukraine and discusses the challenges of applying conditionality to privatization procedures and the implications for country ownership.